Nay Tay a campaign on the use of communication to help increase the level of acceptability of solo parenthood in the Philippines - Lagare, Michelle Sevillo; Tanedo, Jose Alberto (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
Solo parents can be different from single parents. If we say single parents, we are actually talking about a person who is unmarried. Calling them solo parents is more fitting with their situation. Nowadays, solo parents experience maltreatment in the form of discrimination. Even in today's time, our society is still having difficulty in terms of the acceptability of such kind of family. There still exists a notion that a functional family is to be composed of a mother and a father, when in reality; the number of solo parents here in the Philippines is extremely high. Solo parents stand as both the mother and the father in the family, and yet society does not show much appreciation for the hard work they have done for their children.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leave 47.
Keywords: Single parents; Single-parent families